Fibromyalgia: a randomised, controlled trial of a treatment programme based on self management. Issue 3 (12th February 2004) - Cedraschi, C; Desmeules, J; Rapiti, E; Baumgartner, E; Cohen, P; Finckh, A; Allaz, A F; Vischer, T L
Abstract : Objective: To evaluate the efficacy of a treatment programme for patients with fibromyalgia (FM) based on self management, using pool exercises and education. Methods: Randomised controlled trial with a 6 month follow up to evaluate an outpatient multidisciplinary programme; 164 patients with FM were allocated to an immediate 6 week programme (n = 84) or to a waiting list control group (n = 80). The main outcomes were changes in quality of life, functional consequences, patient satisfaction and pain, using a combination of patient questionnaires and clinical examinations. The questionnaires included the Fibromyalgia Impact Questionnaire (FIQ), Psychological General Well-Being (PGWB) index, regional pain score diagrams, and patient satisfaction measures. Results: 61 participants in the treatment group and 68 controls completed the programme and 6 month follow up examinations. Six months after programme completion, significant improvements in quality of life and functional consequences of FM were seen in the treatment group as compared with the controls and as measured by scores on both the FIQ (total score p = 0.025; fatigue p = 0.003; depression p = 0.031) and PGWB (total score p = 0.032; anxiety p = 0.011; vitality p = 0.013, ). All four major areas of patient satisfaction showed greater improvement in the treatment than the control groups; between-group differences were statistically significant for "control of symptoms", "psychosocial factors", and "physical therapy" No change in pain was seen. Conclusion: A 6 week self management based programme of pool exercises and education can improve the quality of life of patients with FM and their satisfaction with treatment. These improvements are sustained for at least 6 months after programme completion.